A Proline-Rich Element in the Type III Secretion Protein FlhB Contributes to Flagellar Biogenesis in the Beta- and Gamma-Proteobacteria - Hook, John C.; Blagotinsek, Vitan; Pané-Farré, Jan; Mrusek, Devid; Altegoer, Florian; Dornes, Anita; Schwan, Meike; Schier, Lukas; Thormann, Kai M.; Bange, Gert (Frontiers in Microbiology, 2020)
Flagella are bacterial organelles of locomotion. Their biogenesis is highly coordinated in time and space and relies on a specialized type III secretion (fT3SS) system required for the assembly of the extracellular hook and filament parts of this complex motor device. The fT3SS protein FlhB switches secretion substrate specificity once the growing hook reaches its determined length. Here we present the crystal structure of the cytoplasmic domain of the transmembrane protein FlhB. The structure reveals a so-far unrecognized proline-rich region (PRR) at the very C-terminus of the protein. Strains lacking the PRR show a decrease in flagellation as determined by hook- and filament staining, indicating a role of the PRR during assembly of the hook and filament structures. Phylogenetic analysis shows that the PRR is a primary feature of FlhB proteins of flagellated beta- and gamma-proteobacteria. Taken together, our study adds another layer of complexity and organismic diversity to the process of flagella biogenesis.